Islamic Stock Indices and COVID-19: Evidence from Indonesia - Cipto, Selamet Herman; Endri, Endri; Haryono, Yono; Hartanto, Dhanang (International Journal of Economics and Financial Issues, 2024)
The COVID-19 pandemic has paralyzed the economy, affected human health, and claimed human lives in the world. This deadly virus is rapidly affecting every aspect of life in all countries. Almost every area of ​​life, from economics to politics, society to culture, has been affected by the COVID-19 pandemic; of course, this impact cannot be separated from the Sharia stocks sub-sector in Indonesia. This study aims to analyze and test the effects of COVID-19 on the response of Islamic stocks. Moreover, to see the difference between the Jakarta Islamic Index (JII) sharia stocks and the Composite Stock Price Index (IHSG) in observations before COVID-19 and after COVID-19. This event study research aims to see the differences between the Jakarta Islamic Index (JII) sharia stocks and the Jakarta Composite Index (IHSG) in observations before COVID-19 and observations after COVID-19. The data used in this study is secondary data already available and obtained from the Indonesia Stock Exchange (IDX). The results of this study show a significant influence on stock prices before and after the announcement of COVID-19 in Indonesia on the Jakarta Islamic Index (JII). There is no significant effect on stock returns before and after the announcement of COVID-19 in Indonesia on the Jakarta Islamic Index (JII). There is no significant effect on abnormal returns before and after the announcement of COVID-19 in Indonesia on the Jakarta Islamic Index (JII). There was a significant influence on stock trading volume before and after the announcement of COVID-19 in Indonesia on the Jakarta Islamic Index (JII).